2021
DOI: 10.3390/en14206464
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Extent of the Rock Destruction Zones around a Gasification Channel on the Basis of Strength Tests of Sandstone and Claystone Samples Heated at High Temperatures up to 1200 °C and Exposed to Water

Abstract: This article presents the results of laboratory tests regarding the influence of high temperatures on changes in the strength and structural parameters of rocks that are present in the immediate vicinity of a gasification channel. Sandstone and claystone samples were heated at 300 °C, 600 °C, 900 °C and 1200 °C. Additionally, the heated samples were placed in water for 24 h. The results of the laboratory tests were used in the numerical simulation using RS2 software. The main goal of modeling was to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 36 publications
(35 reference statements)
0
12
0
Order By: Relevance
“…No. 13 In order to fully compare the illustrations, the stratum's tensile ratio of each layer of the rock formation was calculated, and the fitted curve of the stratum's tensile ratio of the rock formation versus the height of the rock formation was plotted, as shown in Figure 3. According to Figure 3, the stratum's tensile ratio is a negat of the rock layer height.…”
Section: Calculation Of the Height Of The Water-conducting Fracture Z...mentioning
confidence: 99%
See 1 more Smart Citation
“…No. 13 In order to fully compare the illustrations, the stratum's tensile ratio of each layer of the rock formation was calculated, and the fitted curve of the stratum's tensile ratio of the rock formation versus the height of the rock formation was plotted, as shown in Figure 3. According to Figure 3, the stratum's tensile ratio is a negat of the rock layer height.…”
Section: Calculation Of the Height Of The Water-conducting Fracture Z...mentioning
confidence: 99%
“…Scholars have studied the development laws of water-conducting fracture zones through various means [4][5][6][7][8][9][10][11][12], and have proposed various methods to predict the development height of water-conducting fracture zones. Skrzypkowski et al [13] conducted laboratory tests examining the effects of the strength and structural parameters of rocks, and the results showed that water contributes to the weakening of the strength parameters of rocks. Shi et al [14] deduced the prediction formula for the height of water-conducting fracture zones considering mining height, mining depth, and overburden combination characteristics based on the theory of the "upper four zones" of the roof of the quarry.…”
Section: Introductionmentioning
confidence: 99%
“…Article [8] presents the results of laboratory tests regarding the influence of high temperatures on changes in the strength and structural parameters of rocks that are present in the immediate vicinity of a gasification channel. Sandstone and claystone samples were heated at 300 • C, 600 • C, 900 • C, and 1200 • C. Additionally, the heated samples were placed in water for 24 h. Strength tests regarding sandstone and claystone were carried out in a hydraulic press at the laboratory of the Faculty of Civil Engineering and Resource Management at the University of Science and Technology in Krakow.…”
Section: Special Issue Articles' Short Reviewmentioning
confidence: 99%
“…With the increasing energy demand, exploring resources at a significant depth to access geothermal, 1,2 underground coal gasification, [3][4][5] and minerals, as well as storing nuclear waste deep underground, attracts increasing attention. 1,[5][6][7][8] The deep underground has some completely different environmental characteristics, compared with shallow layers, for example, the high temperature rising by 0.3-0.4 C/km 9 and the widely distributed groundwater.…”
Section: Introductionmentioning
confidence: 99%